Researching social work practice close up: using ethnographic and mobile methods to understand encounters between social workers, children and families - Ferguson, Harry (Oxford University Press, 2014)
Research into child and family social work has largely stopped short of getting close enough to practice to produce understandings of what goes on between social workers and service users. This is despite the known problems in social worker engagement with children in cases where they have died. This paper outlines and analyses the methods used in a study of social work encounters with children and families on home visits where there were child protection concerns. It illustrates how mobile methods of walking and driving interviews were conducted with social workers on the way to and from home visits, and how the ethnography involved participant observation and audio-recordings ofthe interactions between social workers, children and parents in the home, re¬vealing the talk, actions and experiences that occurred. Social workers often moved around the home, especially to interview children on their own in their bedrooms, and the paper shows how ways were found to stay close enough to observe these sensitive encounters within families’ most intimate spaces, while ensuring the research remained ethical. Ethnographic and mobile methods produce vital data that advance new understandings of everyday social work practices and service users’ experiences and of dynamics that are similar to breakdowns in practice that have occurred in child death cases.